THE INFLUENCE OF FAMILY ENVIRONMENT AND SOCIAL MEDIA MARKETING ON BUSINESS PERFORMANCE THROUGH ENTREPRENEURIAL ORIENTATION IN SMALL MICRO ENTERPRISES (MSES) IN MAKASSAR CITY - Muhammad Kadafi Burhan; Muhammad Ali; Mursalim Nohong (YUME : Journal of Management, 2020)
This study intends to determine the performance of businesses in small micro enterprises (MSEs) through the influence of the family environment and social media marketing through entrepreneurial orientation. This research was conducted using a quantitative approach that intends to explain the position of the variables studied as well as the relationship between one variable and another. The population of this study is the total number of micro and small businesses in the city of Makassar amounted to 9,958 businesses. The sample in this study used Slovin formula so that it was obtained into 99 respondents. The testing of analysis tools used is path analysis. The results of the study are variable family environment partially positively and significantly affect the orientation of entrepreneurship in micro and small businesses in the city. Social media marketing variables partially have a positive and significant effect on the orientation of entrepreneurship in micro and small businesses in the city of Makassar. Family environment variables partially have a positive and significant effect on the performance of micro and small businesses in the city of Makassar. Social media marketing variables partially affect the positive and significant performance of micro and small businesses in makassar city. The variable orientation of entrepreneurship partially positively and significantly affects the performance of micro and small businesses in the city of Makassar. Family Environment Variables partially have a positive and significant effect on the performance of micro and small businesses in the city of Makassar if through entrepreneurial orientation. And social media marketing variables partially have a positive and significant effect on the performance of micro and small businesses in the city of Makassar if through entrepreneurial orientation, which means the better social media marketing will improve business performance through entrepreneurial orientation. Keywords: Business Strategy, Business Performance, Entrepreneurial Orientation, Social Media Marketing, Family Environment